Numerical and experimental establishment of kiln drying schedule for Iranain beech based on diffusion theory - Mehrabi Madhoshi (Regional Information Center for Science and Technology (RICeST), 2017)
In order to establish a kiln drying schedule for Iranian Beech (Fagus orientalis) lumbers of 5.5 cm thickness, commercially cut from Shast Kola region , 5 km distance from Gorgan. They were then dried under the program based on diffusion theory (from Malmquist's relations) were adopted to dry the lumbers to the final moisture content of 12±2 %. This program for three separate kiln charges and initial moisture content 66.6, 58 and 45 percent was developed. Initial drying bulb temperature (first step) 46 °C and wet-bulb temperature 45 °C was calculated and in three schedules were same. The severity of surface, end checks and warp (bowing, crooking, twisting) in the lumbers were measured before and after the drying process and quality control methods were used to analyze the wood defects. Results indicated that drying of beech lumber using this new schedule was satisfactory. Also intensity changes of defect in all three repeats were about acceptable quality and quantity. Superior characteristics of this program was no surface checks in samples because the moisture content was reduced slowly.